Is freedom of expression associated with economic prosperity? Evidences from 21st century - Shapkova Kocevska, Katerina (Правен факултет „Јустинијан Први“, Универзитет „Св. Кирил и Методиј“ - Скопје, 2018)
Freedom of expression is one of the basic human rights. The Universal Declaration of Human Rights defines freedom of expression as the right of every individual to hold opinions without interference and to seek, receive and impart information and ideas through any media and regardless of frontiers. Freedom of expression in the 21st century is unattainable without existence of free and independent media. The main hypothesis tested in this paper is that countries where freedom of expression is nurtured present higher level of economic prosperity. As a measurement of freedom of expression, we use the World Press Freedom Index, published by the Reporters of the World. This index presents the degree of freedom available to journalists. In 2017, the index was constructed based on answers of experts to a questionnaire answered in 180 countries around the world. The topics covered in this questionnaire include pluralism, media independence, media environment and self-censorship, legislative framework, transparency, and the quality of the infrastructure that supports the production of news and information. Economic prosperity, on the other hand, is broad and heterogeneous concept. Here we assume different aspects concerning the economic wellbeing in the countries around the world. Our focus is on the production, employment, investment, exports and poverty. In our analysis we use different indicators that capture the above-mentioned areas. All of the indicators are published regularly on annual base in the World Development Indicators in the World Bank Database.
Keywords: Freedom of expression; Economic prosperity; World Press Freedom Index